(untitled) (Research, Society and Development, 2024)
The construction industry constantly seeks to improve its techniques, driven by new technologies. In this context, composite materials gain prominence. Materials such as carbon fibers and steel fibers are used to increase the mechanical resistance of structures without changing other parameters such as self-weight. This article sought to analyze and compare the use of steel fibers and carbon fibers as structural reinforcement in civil construction. Furthermore, the research sought to show the use and potential of fibers in concrete. For this, a narrative review methodology of works already carried out and published on the topic was used, in order to obtain the maximum amount of information applied on this subject. Soon after, a comparison was made of the aspects of both materials, as well as their viability and their expression of results. Thus, it was possible to point out the individual characteristics and demonstrate the functionalities of each of the fibers, for different types of works. The comparison between carbon fibers and steel reveals that, although both present improvements, steel fiber offers more agility due to easy workability and better cost-benefit, in addition to the fact that its presence on the market is more common compared to carbon fibers.